2017
DOI: 10.1542/hpeds.2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Asthma Standardized Clinical and Management Plan Reduces Duration of Critical Asthma Therapy

Abstract: A Critical Asthma SCAMP was effective in decreasing time on continuous albuterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…Overall, each PICU cares for a small number of heterogeneous patients with relatively rare diseases, which emphasizes the need for international collaboration. An integral approach to improve care could be realized through a standardized clinical assessment and management plan (SCAMP) and might provide evidence of the effectiveness of these therapies [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, each PICU cares for a small number of heterogeneous patients with relatively rare diseases, which emphasizes the need for international collaboration. An integral approach to improve care could be realized through a standardized clinical assessment and management plan (SCAMP) and might provide evidence of the effectiveness of these therapies [8].…”
Section: Discussionmentioning
confidence: 99%
“…Most pediatric asthma guidelines offer evidence-based approaches to the management of asthma exacerbations (oxygen, inhaled beta-agonists, and systemic corticosteroids). However, they struggle with an evidence-based approach for SAA beyond these initial steps [8][9][10]. There is a broad arsenal of adjunct therapies in case the child is not responding to conventional treatment, but the evidence is often unclear, conflicting or absent in the context of PICU care in literature.…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary group that consisted of pediatric hospitalists, nurses, respiratory therapists, and a pharmacist reviewed and modified the original pathway from Wong et al 19 Changes included the identification of inclusion criteria, definition of transfer criteria, and reduction of the threshold for the administration of heliox. In the pathway, the use of continuous albuterol, intravenous steroids, intravenous magnesium, and heliox as an augmentative therapy was standardized.…”
Section: Interventionmentioning
confidence: 99%
“…16 However, there remains some uncertainty about how and when to initiate these augmentative therapies, and limited data about their efficacy exist. 17,18 In a 2017 study, Wong et al 19 showed a reduction in the length of time on continuous albuterol using a stepwise approach to therapy escalation driven by an asthma severity score. A subsequent iteration of that pathway resulted in a significant decrease in LOS and time to albuterol administered every 4 hours (q4h), which is a proxy of clinical recovery and discharge readiness.…”
mentioning
confidence: 99%
See 1 more Smart Citation